Back Cover: Investigation of the role of template features on the electrically induced structure formation (EISF) for a faithful duplication. Issue 8 (April 2017) - Tian, Hongmiao; Shao, Jinyou; Chen, Xiaoliang; Jiang, Wei; Wang, Li; Ding, Yucheng
Abstract : Electrophoresis 2017, 38, 1105–1112. DOI:10.1002/elps.201700032 The back cover picture shows the technique of the electrically induced structure formation (EISF). In this process, an electrostatic pressure will be generated at the air‐polymer interface to drive the polymer to overcome the surface tension and viscous force to move upwards as the distribution of the modulated electric field determined by the patterned template, leading to a micro‐/nanostructure positive to the template features. As a physical fabrication, the EISF can remove the disadvantages incurred by conventional chemical or plasma etching, which are highly desirable for some polymer devices.